2021
DOI: 10.1038/s41593-021-00865-x
|View full text |Cite
|
Sign up to set email alerts
|

Collicular circuits for flexible sensorimotor routing

Abstract: Historically, cognitive processing has been thought to rely on cortical areas such as prefrontal cortex (PFC), with the outputs of these areas modulating activity in lower, putatively simpler spatiomotor regions, such as the midbrain superior colliculus (SC). Using a rat task in which subjects switch rapidly between task contexts that demand changes in sensorimotor mappings, we report a surprising role for the SC in non-spatial cognitive processes. Before spatial response choices could be formed, neurons in SC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 74 publications
0
38
0
Order By: Relevance
“…Neural inactivation studies have reported varying degrees to which different areas of the neocortex are required during delayed decision-making tasks [37][38][39][40][41][42] . Using our two-task design, we were able to isolate the inactivation effects that were specific to visual working memory, and this revealed the contribution of multiple cortical areas (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural inactivation studies have reported varying degrees to which different areas of the neocortex are required during delayed decision-making tasks [37][38][39][40][41][42] . Using our two-task design, we were able to isolate the inactivation effects that were specific to visual working memory, and this revealed the contribution of multiple cortical areas (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The role of different brain regions in maintaining memory-related task variables has previously been examined by optogenetic inactivation experiments [37][38][39][40][41][42] . To assess which cortical areas were required for working memory and to distinguish between their sensory, mnemonic and motor functions, we transiently inactivated one of six different cortical areas during one of two epochs per trial by focal optogenetic stimulation of inhibitory neurons (see Methods).…”
Section: Working Memory Is Maintained By Distributed Areasmentioning
confidence: 99%
“…Planned movements that are released by a contextual ''Go cue'' are faster and more precise than unplanned movements (Hanes and Schall, 1996;Rosenbaum, 1980;Shenoy et al, 2013;Duan et al, 2021). Planned movements are anticipated by slowly varying neuronal activity in multiple connected brain areas, including the motor cortex (MCx), non-sensory thalamus, and others (Tanji and Evarts, 1976;Tanaka, 2007;Shenoy et al, 2013;Guo et al, 2017Guo et al, , 2018Svoboda and Li, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The motor planning mode collapses (Funahashi et al, 1989;Shadlen and Newsome, 2001;Kaufman et al, 2016Kaufman et al, , 2014, and a new activity mode with multi-phasic dynamics emerges (Churchland et al, 2012). This movement-type-specific mode is preferentially represented in the descending MCx neurons that project to premotor neurons in the brainstem and spinal cord (Li et al, 2015;Economo et al, 2018;Duan et al, 2021) and presumably serves as part of a motor command to initiate a specific movement. Another activity mode after the Go cue consists of changes that are invariant to the movement type (condition-invariant signal; Kaufman et al, 2016), referred to here as ''Go cue direction'' (D go ) mode.…”
Section: Introductionmentioning
confidence: 99%
“…The different patterns of neuronal population activity in the motor cortex, thalamus, brainstem, and spinal cord are related to motor planning and execution. 2 , 3 However, to understand how neuronal dynamics in the cortex trigger motor execution, it is essential to explore the mechanism underlying the transition between those different modes in response to contextual Go cues (Fig. 1 ).…”
mentioning
confidence: 99%